Delivering business intelligence with Microsoft SQL server 2012 - Larson, Brian , 1984- (McGraw-Hill, 2012)
This popular and practical guide, now in its third edition, covers the entire Microsoft BI lifecycle and explains how to build robust data integration, reporting, and analysis solutions.